The effect of complex pharmacotherapy regimens using a herbal remedy from Hippophae rhamnoides on biochemical blood parameters of rats with paracetamol hepatitis - S. Yu. Batueva; G. P. Lamazhapova; Yu. A. Kapustina; O. A. Rodnaeva; S. A. Chukaev (Acta Biomedica Scientifica, 2024)
Background. The use of complexes of synthetic and herbal remedies as hepatoprotectors in the treatment of liver pathologies of various etiologies is an urgent task of pharmacology. A promising type of medicinal plant raw material is an extract of  Hippophaes rhamnoides leaves. The  hepatoprotective effect of extract of  Hippophaes rhamnoides leaves in combination with ademethionine has not been studied to date.The aim of the research was to study changes in biochemical markers of hepatic function in the application of complex schemes of pharmacotherapy of experimental liver damage with paracetamol using Extractum foliorum Hippophaes rhamnoides.Materials and methods. The experimental study was performed on Wistar rats, the  animals were divided into six groups. Group  1 (intact) – animals without a model of liver damage and without treatment; in Group 2 (control) paracetamol was used to create experimental hepatitis without treatment (positive control group); in  Group  3 (comparison) a combination of “silibinin  +  ademethionine” was used on a model of paracetamol hepatitis; in Group 4 (experimental) extract of Hippophaes rhamnoides leaves was used on the model of paracetamol hepatitis; in  Group  5 (experimental) ademethionine was used on a model of paracetamol hepatitis; in Group 6 (experimental) a combination of extract of Hippophaes rhamnoides leaves and ademethionine was used on a model of paracetamol hepatitis. The functional state of the liver of experimental animals was determined by biochemical parameters.Results. When using a combination of extract of Hippophaes rhamnoides leaves with ademethionine, the studied biochemical parameters significantly (p  <  0.05) differed from the numerical values in the negative control group and were closest to those in the intact group than in other experimental groups.Conclusions. A comparison of the effectiveness of the use of extract of Hippophaes rhamnoides leaves in combination with ademethionine by the total effect on blood biochemical parameters determines this complex as a promising drug for further research.